(untitled) (International Journal of Environmental Sciences, 2025)
Eco-tourism has emerged as a vital component of sustainable tourism, aiming to preserve natural ecosystems while providing enriching and responsible travel experiences. As eco- tourism destinations continue to gain popularity, especially in ecologically sensitive regions like Kodaikanal, ensuring a positive tourist experience becomes essential for long-term sustainability. However, the perceived image of a destination and the adequacy of supporting infrastructure play a pivotal role in shaping tourist satisfaction. This study investigates the influence of destination image and infrastructure constraints on tourist satisfaction in Kodaikanal, a well-known eco-tourism hotspot in Tamil Nadu, India. The research is grounded in primary data collected through a structured questionnaire from 150 tourists visiting the region. The study applies Exploratory Factor Analysis (EFA) to identify key components of perceived destination image, including natural scenery, environmental cleanliness, and cultural authenticity. Tourist satisfaction is assessed in relation to various service elements such as accommodation, sanitation, food facilities, and transport services. Additionally, infrastructure- related challenges—such as traffic congestion, improper waste disposal, and inadequate public amenities—are evaluated for their impact on the tourist experience. Descriptive statistics and ANOVA are used to explore differences in satisfaction across demographic groups, while Multiple Regression Analysis is employed to assess the predictive relationship between infrastructure constraints and overall satisfaction levels. The findings reveal that both destination image and infrastructure quality significantly affect tourist satisfaction, with infrastructure constraints emerging as a critical deterrent. The study concludes that addressing infrastructure-related issues and enhancing the perceived image of eco-tourism destinations are essential for improving visitor satisfaction and promoting revisit intention.